Implementation of value stream mapping to reduce waste in a textile products industry. Issue 1 (1st January 2020) - Suhardi, Bambang; Hermas Putri K.S, Maudiena; Jauhari, Wakhid Ahmad
Abstract: Wastes in a production line of a bra model in a textile and textile products industry were identified, and this study aims at minimizing them, and by consequence delays in the delivery of products to consumers. The type of waste was identified employing the Waste Assessment Model approach, and the results show that unnecessary motion is the most predominant one. By eliminating and simplifying activities are not value-added, it was possible to accelerate the production time of the model Bra by 3 minutes and increase the average value of line efficiency by 6.17%.